Biochemical characterization of plasmodium falciparum heat shock protein 70 - Matambo, Tonderayi Sylvester (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2004)
Plamodium falciparum heat shock protein (PfHsp70) is believed to be involved in the cytoprotection of the malaria parasite through its action as a molecular chaperone. Bioinformatic analysis reveal that PfHsp70 consists of the three canonical Hsp70 domains; an ATPase domain of 45 kDa, Substrate binding domain of 15 kDa and a C-terminal domain of 10 kDa. At the C-terminus there is a GGMP repeat motif that is commonly found in Hsp70s of parasitic origins. Plasmodium falciparum genome is 80% A-T rich, making it difficult to recombinantly express its proteins in Escherhia coli (E. coli) as a result of rare codon usage. In this study we carried out experiments to improve expression in E. coli by inserting the PfHsp70 coding region into the pQE30 expression vector. However multiple bands were detected by Western analysis, probably due to the presence of rare codons. The RIG plasmid, which encodes tRNAs for rare codons in particular Arg (AGA/AGG), Ile (AUA) and Gly (GGA) was engineered into the E. coli strain resulting in production of full length PfHsp70. Purification was achieved through NiÂ²â º Chelating sepharose under denaturing conditions. PfHsp70 was found to have a very low basal ATPase activity of 0.262 Â± 0.05 nmoles/min/mg of protein. In the presence of reduced and carboxymethylated lactalbumin (RCMLA) a 11-fold increase in ATPase activity was noted whereas in the presence of both RCMLA and Trypanosoma cruzi DnaJ (Tcj2) a 16-fold was achieved. For ATP hydrolysis kcat value of 0.003 minâ »Â¹ was obtained whereas for ADP release a greater kcat value of 0.8 minâ »Â¹ was obtained. These results indicated that rate of ATP hydrolysis maybe the rate-determining step in the ATPase cycle of PfHsp70.
Keywords: Plasmodium falciparum; Malaria -- Prevention; Protein folding; Proteins -- Purification; Heat shock proteins